2014
DOI: 10.1121/1.4896470
|View full text |Cite
|
Sign up to set email alerts
|

Burst spectrum as a cue for the stop voicing contrast in American English

Abstract: Voicing contrasts in stop consonants are expressed by a constellation of acoustic cues. This study focused on a spectral cue present at burst onset in American English labial and coronal stops. Spectral shape was examined for word-initial, prevocalic stops of all three places of articulation in a laboratory production study and a large corpus of continuous read speech. Voiceless labial and coronal stops were found to have greater energy at higher frequencies in comparison to homorganic voiced stops, a differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 44 publications
(66 reference statements)
1
19
0
Order By: Relevance
“…Such studies have not only proven to give reasonable results, direct comparisons of performance on web-and lab-based experiments showed that they are quite comparable, and as the population is more representative, they even generalize better to the real world (Buhrmester et al, 2011;Crump et al, 2013;Horton et al, 2011;Mason and Suri, 2012). Furthermore, M-Turk has been used successfully in previous speech perception studies as well, and again, when performance was compared to lab-based experiments, the same effects replicated across platforms (e.g., Chodroff and Wilson, 2014;Kleinschmidt and Jaeger, 2012;Yu and Lee, 2014). 3 We specifically designed the study such that the real words would always have a tap, because we wanted to ensure that the predicted increase in trill selection in the Unspecified European Language condition as a result of a higher proportion of Spanish speakers in the community could not be a consequence of having heard those words previously.…”
Section: Discussionmentioning
confidence: 62%
“…Such studies have not only proven to give reasonable results, direct comparisons of performance on web-and lab-based experiments showed that they are quite comparable, and as the population is more representative, they even generalize better to the real world (Buhrmester et al, 2011;Crump et al, 2013;Horton et al, 2011;Mason and Suri, 2012). Furthermore, M-Turk has been used successfully in previous speech perception studies as well, and again, when performance was compared to lab-based experiments, the same effects replicated across platforms (e.g., Chodroff and Wilson, 2014;Kleinschmidt and Jaeger, 2012;Yu and Lee, 2014). 3 We specifically designed the study such that the real words would always have a tap, because we wanted to ensure that the predicted increase in trill selection in the Unspecified European Language condition as a result of a higher proportion of Spanish speakers in the community could not be a consequence of having heard those words previously.…”
Section: Discussionmentioning
confidence: 62%
“…The average value is higher (6.5kHz) than the average COG for the /t/-burst in English (4.5 -5kHz) [31,32]. The probable place of articulation of the clicks observed in our speaker is anterior.…”
Section: Discussionmentioning
confidence: 82%
“…Articulatorily speaking, the production of voiced obstruents requires expansion of supralaryngeal cavity (Ohala, 1983a;Proctor, Shadle, & Iskarous, 2010; J. R. Westbury, 1983)-this expansion occurs because it is necessary to keep the intraoral airpressure sufficiently low with respect to the subglottal airpressure level in order to sustain vocal fold vibrations (Ohala, 1983a). Acoustically speaking, voiced obstruents involve low frequency energy in three respects: (1) they are characterized by low f0 as well as low F1 in surrounding vowels (Kingston & Diehl, 1994, 1995, (2) burst energies are lower for voiced obstruents than for voiceless obstruents (Chodroff & Wilson, 2014), and (3) at least intervocalically, voiced obstruents are characterized by low frequency energy which reflect vocal fold vibration (a 'voice bar') (Stevens & Blumstein, 1981). These low frequency properties, which are demonstrably integrated into one perceptual property (Kingston & Diehl, 1995;Kingston, Diehl, Kirk, & Castleman, 2008), can be mapped onto large images, because of the general inverse relationship between the size of a resonator and its resonating frequency (Ohala, 1983b(Ohala, , 1994.…”
Section: Introductionmentioning
confidence: 99%